Cross‐sectional trends in HIV prevalence among pregnant women in Botswana: an opportunity for PrEP?. Issue 3 (24th March 2022) - Kapoor, Andrew; Mussa, Aamirah; Diseko, Modiegi; Mayondi, Gloria; Mabuta, Judith; Mmalane, Mompati; Makhema, Joseph; Morroni, Chelsea; Lockman, Shahin; Zash, Rebecca; Shapiro, Roger
Abstract: Introduction: Young women in sub‐Saharan Africa are at particularly high risk of HIV acquisition. Recent shifts towards "test and treat" strategies have potential to reduce transmission in this age group but have not been widely studied outside of clinical trials. Using data from nationwide surveillance among pregnant women in Botswana, where a "test and treat" program was implemented in 2016, we describe trends in HIV prevalence over time and highlight opportunities for targeted prevention. Methods: The Tsepamo study abstracted data from obstetric records of all women delivering at eight government hospitals in Botswana between 2015 and 2019, accounting for 45% of all births in the country ( n = 120, 755). We used a stratified analysis to identify prevalence trends and evaluated decreases in HIV prevalence over time using the Cochrane–Armitage test for linear trend. A multivariable logistic regression analysis was also performed to identify factors associated with declines in HIV prevalence. Results: Overall HIV prevalence was 24.1% among 120, 755 women who delivered during the study period. Prevalence differed by site of delivery, ranging from 16.1% to 28.2%, and increased markedly with age. Lower educational attainment (adjusted odds ratio [aOR] = 3.28; 95% confidence interval [CI] 3.07–3.50) and being unmarried (aOR = 1.98; 95% CI 1.88–2.08) were associated with HIV infection. HIV prevalence was 10.0% with a first pregnancy, 21.0% with a second and 39.2% with a third or greater (aOR = 2.20; for any prior pregnancy; 95% CI 2.10–2.29). The same age‐adjusted trends were seen when data were limited to women aged 15–24, with a two‐ to three‐fold increase in HIV prevalence between a first and third pregnancy. Prevalence decreased linearly during the 5‐year study period from 25.8% to 22.7% ( p <0.001). Among age‐specific strata, the greatest absolute decline occurred in those aged 35–39, with an 8.7% absolute decrease in HIV prevalence from 2015 to 2019. Minimal declines were seen in those 15–24, with a decrease of only 1.5% over the same period. Conclusions: While overall trends in Botswana show HIV prevalence declining among pregnant women, prevalence among the youngest age group has remained stagnant. Preventative interventions utilizing pre‐exposure prophylaxis should be prioritized during the high‐risk period surrounding a woman's first pregnancy.